The value of Mental Index (MI) and Gonial Index (GI) in hypertension patients on its correlation with serum calcium and cortisol level - Dwi Putri Wulansari; Lusi Epsilawati; Farina Pramanik; Suhardjo Sitam (Ikatan Radiologi Kedokteran Gigi Indonesia, 2021)
Objective: This research was aimed to analyze the mandibular cortical width based on a mental index (MI) and gonial Index (GI) in hypertension patients correlated with serum calcium and cortisol levels. Materials and Methods: This study was an analytic-observational study with 31 hypertension patients aged 41-79. All of the patients have checked their serum calcium and cortisol level. The panoramic radiograph was taken and analyzed using Image-J Fiji software. The mandibular cortical width was then measured with Mental Index (MI) and Gonial Index (GI) and correlated with the serum calcium and cortisol level. Results: The data obtained from examining serum calcium and cortisol levels and the measurement of Mental Index (MI) and Gonial Index (GI) showed varying results but tended towards normal values. The results of the correlation test between mental index and gonial index with cortisol and serum calcium showed no correlation with p>0.05. Conclusion: There was no correlation between serum calcium and cortisol level in the value of MI and GI in hypertension patients.